Educação física e cidadania : a gestão da Secretaria de Educação do Município de Vitória - Silveira, Ana Carolina Godoi da (2012)
The objective of this research is to understand what are the actions of the Vitória Municipal Secretary of Education (Seme) for Physical Education as a curriculum component acts to promote and ensure citizenship. The relevance of the research is to discuss the importance of citizenship education in school as well as survey data indicate that the actions of the educational administration of the city to ensure that physical education meets one of its objectives: the formation of citizens. This is a qualitative research of an exploratory/descriptive. For the acquirement of informations, we used documents from Seme, and a meeting with a focus group composed for Physical Education teachers who work in administrative Secretariat. The development of the study was conducted in three stages: at first, a literature review was conducted; in the second stage, there was a documentary analysis of the curricular guidelines of the City of Vitória (PMV), and Law 4747/98 establishing the Education System of the City; in the last step, we conducted a focus group with managers from Seme with degrees in Physical Education. The technique used to tabulate the informations, was the content analysis, which provided for a cut of the texts according to content more significant for the later grouping and categorization of units answers. Through the methodological approach described above, it was possible to understand the organization / operation of the Sports Coordinating, as well as their actions towards that Physical Education is recognized as a promoter of citizenship and work with the civic education. Expressions like "citizenship", "justice", "participation" and "emancipation," appear more in the discourse of managers, unless the documents, and almost nothing in the actions. Thus, we point few are the systematized strategies through Seme for the physical education as a curricular component, can cooperate with the citizenship formation.